2019
DOI: 10.1038/s41598-018-36186-6
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization provides support for obesity as a risk factor for meningioma

Abstract: Little is known about the causes of meningioma. Obesity and obesity-related traits have been reported in several epidemiological observational studies to be risk factors for meningioma. We performed an analysis of genetic variants associated with obesity-related traits to assess the relationship with meningioma risk using Mendelian randomization (MR), an approach unaffected by biases from temporal variability and reverse causation that might have affected earlier investigations. We considered 11 obesity-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Positive associations with meningioma risk were identified in body mass index (BMI) and body fat percentage [ 25 ]. The summary relative risk (RR) of meningiomas with respect to BMI was 1.48 (95% CI, 1.30–1.69) for obesity and 1.18 (95% CI, 1.07–1.31) for those overweight [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive associations with meningioma risk were identified in body mass index (BMI) and body fat percentage [ 25 ]. The summary relative risk (RR) of meningiomas with respect to BMI was 1.48 (95% CI, 1.30–1.69) for obesity and 1.18 (95% CI, 1.07–1.31) for those overweight [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a dose-response analysis, for every 5 kg/m 2 increment of BMI, the summary RR was 1.19 (95% CI, 1.14–1.25) for meningiomas [ 26 ]. Proposed mechanisms for the association of obesity with increased meningioma risk include chronic inflammation and increased adipokine-mediated signaling, as well as insulin signaling and insulin-like growth factor (IGF) signaling [ 25 ]. IGF-1 is known to suppress apoptosis and stimulate tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MR design and IPW based on pre-disease background characteristics in the analysis of BSI mortality among BSI patients reduces the risk of selection bias. The genetic instrument for BMI that we used has been successfully applied in other recently published MR studies [41,42]. Importantly, although it is recommended that researchers create the genetic instrument based on the full set of SNPs associated with the desired exposure, this may increase the risk of pleiotropic effects and affect causal inference [24].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Furthermore, a genotype analysis in 65 samples using high-density single nucleotide polymorphism (SNP) arrays found associations between meningiomas and variation in PIAS2, KATNAL2, TCEB3C, TCEB3CL , and CTNNA3 , especially TARDBP mutations with amyotrophic lateral sclerosis ( 21 ), which further improves the identification of susceptible sites of meningioma by genomics. Subsequently, a GWAS involving 1,606 meningioma patients and 9,823 controls provided additional support for the link between obesity and risk of recurrence in meningioma ( 22 ), which laid a solid foundation for meningioma characteristics, including risk factors and epidemiology ( 23 , 24 ). To further illustrate the genetic basis and construct a genetic linkage map of meningioma, Claus et al identified a new meningioma susceptibility site at 11p15.5 through a combined reference panel from UK10K data including a total of 2,138 and 12,081 controls and 1,000 genomic projects in 2018 ( 25 ).…”
Section: Genomicsmentioning
confidence: 99%